(untitled) (Archives of Clinical and Medical Case Reports, 2021)
Déjà vécu is an extremely rare type of identifying paramnesia characterised by the ongoing sensation of having experienced things before. Having the delusional conviction that this sensation is true, patients frequently exhibit recollective confabulation. We here describe an 84-year-old woman with idiopathic, partial déjà vécu, where her symptoms were limited to people and events. An extensive psychiatric and somatic work-up ruled out cerebrovascular disease, epilepsy, dementia, psychosis, or intoxication as a potential underlying cause. Proposed to be a functional disturbance of the limbic system with the involvement of a network that comprises at least the hippocampus and entorhinal cortex, the pathophysiology of déjà vécu is in need of further elucidation. Our patient and her family were offered psychoeducation, which led to acceptance and improved coping. During the two-year follow-up, the déjà vécu sensations continued unaltered, but all involved were less bothered by them, with the patient’s functioning improving both personally and socially.